1993
DOI: 10.1111/j.1530-0277.1993.tb00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐Induced Inhibition of Alveolar Macrophage Oxidant Release in Vivo and in Vitro

Abstract: Alcohol consumption is known to predispose the host to more frequent and severe bacterial infections, suggesting that alcohol compromises the normal immune function of the lung. The pulmonary alveolar macrophage is the resident host defense cell in the lung and forms the first line of defense against invading microorganisms. One of the mechanisms whereby alveolar macrophages kill bacteria is by releasing toxic oxygen radical species, such as superoxide anion and hydrogen peroxide. We hypothesized that chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…So the decrease in liver RES function could be one important factor in the pathogenesis of biliary pancreati tis. This is especially interesting in context with the finding that macrophage function can also be diminished by ethanol application [26,27], showing a parallel to alcohol-induced pancreatitis.…”
Section: Discussionmentioning
confidence: 94%
“…So the decrease in liver RES function could be one important factor in the pathogenesis of biliary pancreati tis. This is especially interesting in context with the finding that macrophage function can also be diminished by ethanol application [26,27], showing a parallel to alcohol-induced pancreatitis.…”
Section: Discussionmentioning
confidence: 94%
“…In present study, it was also found that phagocytic activity of LPS-activated macrophages also decreased with increasing concentration of alcohol. However, the nitric oxide released on activation of macrophages by lipopolysaccharide shows an increasing trend implying that alcohol causes some injury and thus an increase in release of nitric oxide 2 . Therefore alcohol has a dual effect on immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen radicals produced by macrophages and other phagocytes play a crucial role in destroying micro-organisms, especially in the lungs. Researchers found that macrophages in the lungs of acutely or chronically alcohol-fed rats produced fewer super-oxide anions and less hydrogen peroxide than did macrophages from non-alcohol exposed rats 2 . Furthermore, the lung macrophages produced and secreted less nitric oxide, another molecule with characteristics and functions similar to those of oxygen radicals 3 .…”
Section: Alcohol's Effects On Oxygen-radical Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both acute and chronic ethanol exposure in rats are reported to inhibit the secretion of TNF-␣ and nitric oxide by alveolar macrophages [92,93]. The chronic exposure in the latter study also suppressed the production of the superoxide anion by alveolar macrophages [92]. Further evidence of ethanol immunosuppression is that splenocytes and thymocytes of chronic ethanol-exposed mice had reduced mitogen-stimulated production of IL-2, IL-6, IL-10, IFN-␥, IL-4, and TNF-␣ [94].…”
Section: Ethanol Effects On Brain Immune System Function and The Prmentioning
confidence: 99%